Financial distress prediction in Islamic commercial banks: The role of gender, corporate social responsibility, and capital structure - Muhamad Farhan Auwala; Faqiatul Mariya Waharini (Faculty of Islamic Economics and Business, UIN Salatiga, 2024)
This research empirically tests the influence of women’s presence on the board of directors, Corporate Social Responsibility (CSR) expenditure, and capital structure on the likelihood of financial distress for a sample of 13 Islamic commercial banks in Indonesia from 2019 to 2022. The study employs regression to determine the impact of board gender diversity on financial distress. Altman Z-score model is used as a proxy for financial distress indicator. The result shows that the presence of female director can enhance the possibility of financial distress due to their excessive caution. In addition, CSR can also lead to financial difficulties for the entities because CSR implementations need substantial funding, and undue reliance on debt can also increase the risk of financial problems. These findings have significant implications for governance and risk management in Islamic commercial banks. They stress the need for a balanced approach to board gender diversity, avoiding excessive caution that could lead to financial strain. Banks should align CSR activities with their financial capacity to prevent undue burden and manage debt levels prudently to reduce financial distress. These insights can help policymakers and institutions improve governance, CSR strategies, and financial risk management, enhancing the stability of Islamic commercial banks.